2019
DOI: 10.31832/smj.560336
|View full text |Cite
|
Sign up to set email alerts
|

Transfüzyon Amaçlı Kan Verme Önündeki Engellerin Belirlenmesi

Abstract: Amaç Kan, geçmişten günümüze insan sağlığının ve yaşamın temel simgesi durumundadır. İnsan, kanın tek kaynağıdır. Temini için şimdilik başka bir alternatifte yoktur. Eşsiz bir tedavi aracı olarak da bilinmektedir. Bu bağlamda toplumun kan ve kan ürünleri gereksinimi ve kan bağışı konusunda neleri, ne kadar ve ne derece doğru bildiğinin tespit edilmesi bir gerekliliktir. Bu çalışmada, toplumun transfüzyon amaçlı kan verme önündeki engelleri ve bu konudaki tutum-davranışlarını belirlemek ve kan bağışı ile ilgili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Bourne et al's study conducted with 200 students at the Jamaica University of Technology found that although students had high knowledge and awareness about blood donation, they donated less blood [10]. In Altındiş et al's study conducted with 451 participants, it was revealed that 63% of the participants had never donated blood before [11]. In their study with 176 teacher participants, Hablemitoğlu et al found that blood donation status and age were important predictors [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bourne et al's study conducted with 200 students at the Jamaica University of Technology found that although students had high knowledge and awareness about blood donation, they donated less blood [10]. In Altındiş et al's study conducted with 451 participants, it was revealed that 63% of the participants had never donated blood before [11]. In their study with 176 teacher participants, Hablemitoğlu et al found that blood donation status and age were important predictors [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Yaşar et al with 100 physicians, it was found that 7% of donors avoided donating blood due to fear of contracting an infectious disease [24]. Altındiş et al found that 34.1% of participants experienced fear of infection when donating blood [11]. Ryhan et al in their study where 35,256 donors donated blood, it was determined that 1928 donors experienced negative effects and age and gender were effective in this effect [25].…”
Section: Discussionmentioning
confidence: 99%